Histological clues to the diagnosis of metastasis to the breast from extramammary malignancies. Issue 2 (23rd July 2020) - Lee, Andrew H S; Hodi, Zsolt; Soomro, Irshad; Sovani, Vishakha; Abbas, Areeg; Rakha, Emad; Ellis, Ian O
Abstract: Aims: The aims of this study were to review the histological features useful for the identification of metastases to the breast and to investigate the impression that this diagnosis has become more common. Methods and results: The histological features of metastases to the breast from 2008 to 2018 were reviewed. Seventy‐four biopsies from 66 patients were identified: 1% compared with primary carcinoma of the breast. Non‐haematological metastases comprised 0.75% compared with 0.3% in a series from 1996 to 2005. The most common tumour types were pulmonary carcinoma (22), lymphoma (15), melanoma (13), gastrointestinal carcinoma (eight) and serous papillary carcinoma (four). In 73% there were histological features that were not typical of primary mammary carcinoma. Some metastases were histologically similar to breast cancer and the history was essential to making the correct diagnosis. Useful histological clues included small‐cell morphology for pulmonary carcinoma, glands containing necrosis for gastrointestinal carcinoma, intranuclear inclusions, marked pleomorphism and spindle cells for melanoma, clear cells for renal carcinoma, papillary architecture for serous papillary carcinoma and sheets of centroblasts or nodules of centroblasts and centrocytes for lymphoma. Useful immunohistochemical markers included TTF‐1 for pulmonary carcinoma, S100, melan‐A and HMB45 for melanoma, CK20 and CDX2 for colorectal carcinoma, PAX8 and WT1 for serous papillary carcinoma and lymphoid markers for lymphomas, in addition to the absence of expression of mammary markers ER, GATA3 and GCDFP‐15. Conclusion: The majority of metastases to the breast have histological clues to the diagnosis. Immunohistochemistry is helpful. This diagnosis is being made more frequently.